Student perception of gamekit in game-based learning: impacts on engagement and motivation in english learning - albukhari, Shofia (Maliki Interdisciplinary Journal, 2025)
Game-based learning through Gamekit has emerged as a significant innovation in English language education. This article explores student perceptions of Gamekit implementation and its impacts on engagement and motivation in English learning at MAN Kota Pasuruan. The investigation reveals how digital game-based learning tools influence student participation, interest, and academic performance. Through comprehensive analysis of student experiences, this study demonstrates that Gamekit implementation provides positive effects on student engagement and motivation in English language learning. The findings contribute to understanding the role of educational technology in enhancing language acquisition processes and student-centered learning approaches. This research offers valuable insights for educators and policymakers considering the integration of game-based learning tools in Islamic educational institutions. Future implementations should consider comprehensive teacher training programs, adequate technical infrastructure development, and ongoing evaluation mechanisms to ensure sustained success. The successful integration of educational technology within Islamic educational contexts provides valuable insights for similar institutional settings.The findings suggest that game-based learning tools like Gamekit can effectively complement traditional educational approaches while respecting cultural and religious values. The positive student responses indicate that technological innovation can enhance educational quality without compromising institutional identity or educational principles